Using Problem-Solving Strategies in the Interpretation and Evaluation of Skills Development in Vocational Education in Jordan - Mohammad Omar AL-Momani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study will identify the impact of using problem-solving strategies in developing interpretation and evaluation skills among tenth graders in vocational education in Ajloun governorate, Hashemite Kingdom of Jordan. In this experimental study, the researchers prepared an achievement test that was applied before and after the second semester of the academic year (2021-2022), after confirming its validity and reliability. This study shows that there is no statistically significant difference at the level of significance (α = 0.1) between the mean scores of the experimental group students and the control group students for interpretation skills, which is associated with the application of problem-solving methods. In addition, there is a statistically significant difference at the level of significance (α = 0.1) between the average score of the assessment skills of the experimental group students and the control group students, which is associated with the application of problem-solving methods.Studi ini akan mengidentifikasi dampak penggunaan strategi pemecahan masalah dalam mengembangkan keterampilan interpretasi dan evaluasi di kalangan siswa kelas sepuluh dalam pendidikan kejuruan di provinsi Ajloun, Kerajaan Hashemite Yordania. Dalam penelitian eksperimental ini, peneliti menyiapkan tes prestasi yang diterapkan sebelum dan sesudah semester kedua tahun ajaran (2021-2022), setelah dipastikan validitas dan reliabilitasnya. Penelitian ini menunjukkan bahwa tidak terdapat perbedaan yang signifikan secara statistik pada tingkat signifikansi (α = 0,1) antara nilai rata-rata siswa kelompok eksperimen dan siswa kelompok kontrol untuk keterampilan interpretasi, yang dikaitkan dengan penerapan pemecahan masalah. metode. Selain itu, terdapat perbedaan yang signifikan secara statistik pada tingkat signifikansi (α = 0,1) antara skor rata-rata keterampilan penilaian siswa kelompok eksperimen dan siswa kelompok kontrol, yang dikaitkan dengan penerapan metode pemecahan masalah.